2000
DOI: 10.1088/0964-1726/9/6/313
|View full text |Cite
|
Sign up to set email alerts
|

Detection of transverse cracks in CFRP composites using embedded fiber Bragg grating sensors

Abstract: In the present research, fiber Bragg grating (FBG) sensors were applied for the detection of transverse cracks, which cause strain distribution within the gage length, in carbon fiber reinforced plastic (CFRP) cross-ply laminates. An uncoated FBG sensor was embedded in 0 • ply on the border of 90 • ply in a CFRP cross-ply laminate. The reflection spectra from the FBG sensor were measured at various tensile stresses. As a result, the reflection spectrum became broad and had some peaks with an increase of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(106 citation statements)
references
References 18 publications
6
100
0
Order By: Relevance
“…Meanwhile, the FWHM also displayed an obvious correlation with the crack length until a saturation crack length is reached. The spectrum bandwidth is also directly related to strain distribution and hence has been previously applied [14,15]. A shift of the measured central wavelength of less than 0.1 nm is observed during the process.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the FWHM also displayed an obvious correlation with the crack length until a saturation crack length is reached. The spectrum bandwidth is also directly related to strain distribution and hence has been previously applied [14,15]. A shift of the measured central wavelength of less than 0.1 nm is observed during the process.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon can be used to detect damage in the composite structures [11,12]. But it was reported that the chirp of the FBG spectrum was not limited to stress concentrations [13].…”
Section: Shm For Frp Aerospace Structuresmentioning
confidence: 99%
“…Peters et al (2001) [22] measured reflection spectra in a compact tension specimen with an embedded FBG sensor and simulated the change in the spectrum shape resulting from the large strain gradients. Okabe et al (2000) [11] and Takeda et al (2002) [12] first utilized this feature to detect internal damage in the carbon fiber reinforced polymer (CFRP) laminates. Yashiro et al (2005) [20] also demonstrated that the reflection spectrum of an embedded FBG sensor was useful for identifying damage patterns within the gauge section for notched FRP laminates [23].…”
Section: Use Of Fbg Sensors For Shm In Aerospace Structuresmentioning
confidence: 99%
“…This report shows examples of application to composite materials. 4.2.1 Development of health monitoring technology 22) There is a need to monitor such anomalies as defects and vibrations at all times. It is therefore hoped that optical fibers, piezoelectric elements and electrical resistors and other measuring methods are established.…”
Section: Smart Materials and Structural Systems 21)mentioning
confidence: 99%